2011
DOI: 10.1186/1471-2474-12-54
|View full text |Cite
|
Sign up to set email alerts
|

Adalimumab reduces hand bone loss in rheumatoid arthritis independent of clinical response: Subanalysis of the PREMIER study

Abstract: BackgroundAnti-TNF therapy has been shown to reduce radiographic joint damage in rheumatoid arthritis (RA) independent of clinical response. This has previously not been examined for periarticular bone loss, the other characteristic feature of bone involvement in RA.The objective of this study was to examine if treatment with the TNF-α inhibitor adalimumab also could reduce periarticular bone loss in RA patients independent of disease activity.MethodsRA patients were recruited from the PREMIER study and includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 17 publications
3
27
0
1
Order By: Relevance
“…Recent results from a study of the RANKL inhibitor denosumab further support the important role of the osteoclast, since this drug inhibited erosions and hand DXA-BMD loss, but not cartilage destruction or inflammation [Cohen et al, 2008;Deodhar et al, 2008]. In addition, anti-TNF therapy has been found to decrease hand bone loss independent of disease activity, supporting the hypothesis that TNF has a direct influence on the osteoclast [Hoff et al, 2009d].…”
Section: Predictors Of Hand Bone Loss and The Association With Inflammentioning
confidence: 92%
“…Recent results from a study of the RANKL inhibitor denosumab further support the important role of the osteoclast, since this drug inhibited erosions and hand DXA-BMD loss, but not cartilage destruction or inflammation [Cohen et al, 2008;Deodhar et al, 2008]. In addition, anti-TNF therapy has been found to decrease hand bone loss independent of disease activity, supporting the hypothesis that TNF has a direct influence on the osteoclast [Hoff et al, 2009d].…”
Section: Predictors Of Hand Bone Loss and The Association With Inflammentioning
confidence: 92%
“…Further, a post hoc analysis grouping patients by therapeutic response showed that the protective effect on bone was associated with clinical remission, irrespective of treatment with anti-TNF α [52]. Conversely, a second well-powered randomized clinical trial showed that the anti-TNF α Adalimumab in combination with Methotrexate reduced hand bone loss independently of clinically assessed disease activity and inflammatory status [53], suggesting that the beneficial effects of anti-TNF α therapy could not be limited to the control of inflammation, but also to its ability to inhibit the direct effect of TNF α on osteoclast activation by binding to TNF α receptor placed on osteoclast precursors.…”
Section: Treatment Of Ra With Biologic Drugs and Bone Lossmentioning
confidence: 99%
“…In this trial, hand bone loss was associated with no use of adalimumab, increasing age and inflammation [78]. A sub-analysis of the data showed that patients in the MTX monotherapy group with high/moderate disease activity (DAS28>3.2) or high levels of C reactive protein (CRP≥10 ng/ml) had greater bone loss in the hands compared to those in remission/low disease activity (DAS≤3.2) or low levels of CRP (<10 ng/ml) [79]. In the group receiving both drugs, bone loss was similar regardless of the disease activity and inflammatory status, and was comparable to patients who had low disease activity with MTX only.…”
Section: Anti-tnf Agents and Bone Loss In Patients With Rheumatoid Armentioning
confidence: 99%
“…In the group receiving both drugs, bone loss was similar regardless of the disease activity and inflammatory status, and was comparable to patients who had low disease activity with MTX only. These last findings suggest that the benefits of anti-TNF therapy may not be limited to control of inflammation, but also to the ability to block the direct effect of TNFα on osteoclast activation [79••]. …”
Section: Anti-tnf Agents and Bone Loss In Patients With Rheumatoid Armentioning
confidence: 99%